PEMBERDAYAAN MASYARAKAT BERBASIS PERAIRAN BERKELANJUTAN DALAM PENGOLAHAN RUMPUT LAUT MENJADI CAMILAN CRISPY DI DESA MERTAK - Roendah, Baiq Hildha Aulia; Adinegoro, Cahyo; Abror, Haekal Malik; Putri, Juliana; Maulana, M.Aril; Wibawa, Neorista Anggun; Sahara, Nova Nabila; Sopiani, Rani; Rindiani, Saptia; Rahayu, Sefani Cahyo Auliya; Sudiarta, I Wayan (Jurnal Wicara, 2024)
Mertak Village is a village with a coastal area that has natural tourism potential and is included in the development area of the Mandalika Special Economic Zone in Central Lombok Regency. To increase the participation of the Mertak Village Community, a community service program was initiated which is directly related to the empowerment of the potential in the waters in Mertak Village, especially the development of seaweed through socialization and management strategies and marketing of processed seaweed products. The Mertak Village community empowerment program aims to improve the community's living standards through processing seaweed into healthy crispy. Seaweed is an abundant natural resource potential in Mertak Village, but so far it has not been utilized optimally. Through this program, the people of Mertak Village are given training and assistance in seaweed cultivation, post-harvest processing into crispy snacks, and marketing strategies. The crispy seaweed snacks produced are expected to be a superior product of the village that has a high selling value and is healthy. This empowerment program is expected to have a positive impact on the economy of the people of Mertak Village, as well as increase public awareness of the sustainable use of natural resource potential.